Long-Term Consequences of Parenting by Another Child in a Population with Child Malnutrition - Mery del Carmen Hernández Escalona (2024)
Malnutrition is a pervasive health concern around the world. Its impact is related to its severity, age at which it begins, and duration. As of now, the impact of the mother’s psychological variables on maltrunition have been hardly studied. In particular, research showing the impact of having a mother raised by a child instead of an adult is absent from the literature. The goal of this work was to fill that gap. The sample consisted of 111 mother-child dyads assisting the Argentinean centers, that support families whose children are exposed to resource scarcity conditions and diagnosed with malnutrition. In Particular, we aimed to assess the effect of being reared by a child on future caregiver quality and stress responses, in a population with child malnutrition. Given the absence of previous studies, the nature of the present work was exploratory. We found that mothers that were raised by a child reported higher levels of perceived stress at present and a lower quality of caregiving during infancy. Additionally, they feel incapable of coping with their problems and unable to control the events that affect them. These findings are discussed in the context of Attachment Theory and social buffering.